Versatile water soluble graphene nanoplatelets for water-based polymers - Lim, Hong Ngee (2018)
Water insoluble graphene nanoplatelets was converted to water soluble graphene nanoplatelets (GNPs) by a facile modification method. The water soluble GNPs easily dispersed in water-based polymers such as latex and polyvinyl alcohol with only mild agitation. The GNPs-fortified latex and GNPs-fortified polyvinyl alcohol (PVA) film yielded an average resistance of 1.8 x 104 Ω and 1.4 x 104 Ω, respectively. A mixture of water soluble GNPs and PVA was electrospun to produce a GNPs-fortified PVA nanofibre membrane. Subsequently, the nanofibre membrane was carbonized to produce a GNPs-fortified carbon nanofibre (CNF) membrane. The electrochemical performance of the GNPs-CNF membrane was measured. The current density of GNPs-CNF membrane increased by twofold, and the galvanostatic charge-discharge duration doublefold, as opposed to the neat CNF membrane. The GNPs-CNF membrane achieved an average stability of more than 95% for 1,000 cycles of galvanostatic charge-discharge.